Benefits of an online multimodal nursing program among patients with peripherally inserted central catheter-related thrombosis - Huang, Xin; Xie, Meilian; Zhao, Shan; Chen, Yingtong; Wu, Liying; Zeng, Xiuqun (Frontiers in Public Health, 2022)
Background: Asymptotic peripherally inserted central catheter-related thrombosis (PICC-RT) is one of the most common and dangerous complications caused by peripherally inserted central catheter (PICC) insertion. A variety of factors might lead to huge psychological pressures on patients and markedly affect their quality of life. The aim of this study was to evaluate the benefits of an online multimodal nursing program on the quality of life and psychological resilience of asymptomatic PICC-RT patients with ovarian cancer. Methods: This was a prospective cohort study on patients with asymptomatic PICC-RT. Patients in the control group received routine nursing care, while patients in the intervention group obtained extra assistance through an online multimodal nursing program. Individual guidance, psychological support, and real-time consultation were provided to patients in the intervention group. All participants were followed for 3 months. The health-related quality of life and psychological resilience of patients were evaluated by using the 36-item Short Form Health Survey (SF-36) and Connor-Davidson Resilience Scale (CD-RISC), respectively. Results: Compared to baseline, most of the items in the SF-36 scores were significantly increased in both intervention and control groups after 3 months (all p<0.05), except for the role emotional domain (p=0.085 in control group). However, the SF-36 scores of the intervention group were significantly higher than those of the control group in all health domains, including physical functioning (p=0.001), role physical (p=0.004), bodily pain (p=0.003), general health (p<0.001), vitality (p<0.001), social functioning (p<0.001), role emotional (p=0.002), mental health (p<0.001) and health transition(p<0.001). For CD-RISC scores, the mean value of the control group was 42.03±4.42 at baseline and increased to 50.36±4.70 after 3 months (p<0.001), while the intervention group was 40.00±6.61 at baseline and increased to 65.12±5.21 after 3 months (p<0.001). Moreover, the CD-RISC score in intervention group was significantly higher than that in the control group after 3 months (p<0.001). Conclusion: The application of an online multimodal nursing program could significantly improve the health-related quality of life and psychological resilience of asymptomatic PICC-RT patients. These findings provide evidence to support the necessity of an online multimodal nursing program in routine long-term follow-up, especially in the era of COVID-19.